Μελέτη της σεισμικής συμπεριφοράς πλαισίου από οπλισμένο ελαφροσκυρόδεμα σχεδιασμένου κατά Ευρωκώδικα 2 και 8 - Μάνος, Γεώργιος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών. Τομέας Δομοστατικής. Εργαστήριο Οπλισμένου Σκυροδέματος, 2014)
The usage of lightweight structural concrete in buildings is of significant interest because of its lower self-weight, implying significantly lower gravity and inertial loads under earthquake response. On the other hand, lightweight concrete exhibits a lower modulus of elasticity compared with normal density concrete, resulting to larger vertical and horizontal displacements under similar design loads. Also, its relatively higher brittleness (when unconfined), may require that seismic design loads (moment and shear) as well as the available element plastic rotation, specified in normal weight concrete design, be reconsidered. The primary objective of this thesis is the evaluation of the seismic performance of a lightweight concrete structure, considering the influence of the special characteristics of lightweight concrete under vertical load and earthquake analysis. For this purpose, a typical five story residential building, made of lightweight concrete, is designed for the serviceability and ultimate limit states according to Eurocodes 2 and 8. Also, the same building is designed using normal density concrete for comparison. The comparative designs include (further to the economics and geometric changes associated with the two materials): i) the time varying deformations caused by the vertical loads, considering creep and cracking effects, as well as those which are caused by the seismic lateral loads and ii) the change in the dynamic characteristics of the structure, the post-elastic behavior and the distribution and the state of plastic hinges under inelastic pushover analysis, due to the differences in the concrete characteristics.